Understanding the crystal structure of lotus seed amylose–long-chain fatty acid complexes prepared by high hydrostatic pressure. (September 2018) - Jia, Xiangze; Sun, Siwei; Chen, Bingyan; Zheng, Baodong; Guo, Zebin
Abstract: This paper presents an innovative approach using high hydrostatic pressure to prepare lotus seed amylose–long-chain fatty acid (stearic acid, oleic acid, and linoleic acid) complexes. The aim of this work was to investigate the spherocrystal structure and distribution of fatty acid within complexes. Wide-angle X-ray diffraction diffractograms indicated the presence of typical V6 -type polymorphs and B-type non-complexed amylose. The V6 -type complexes were further confirmed as V6III polymorph from nuclear magnetic resonance. The degree of crystallinity and the complex index value decreased as the preparation pressure of the complexes increased, and the amylose–oleic acid complexes exhibited the highest relative crystallinity and complex index value in all of the conditions. Small-angle X-ray scattering indicated a larger proportion of crystalline and more compact structure within complexes than that of lotus seed amylose. The morphology of complexes with the spherulite form was determined from scanning electron microscopy images, and the distribution of fatty acid molecules within the spherulites of complexes was estimated using nuclear magnetic resonance, confocal laser scanning microscopy, and small-angle X-ray scattering. The results demonstrated that the fatty acids were within and between the amylose helix, and they were also trapped inside the amorphous lamellae of the complexes. This work provides an in-depth study of the spherocrystal structure within lotus seed amylose–long-chain fatty acid complexes and proposes a new model for spherulites. Graphical abstract: Unlabelled Image Highlights: Lotus seed amylose-long-chain fatty acid complexes were prepared by HHP treatment. Spherocrystal structure and distribution of fatty acid of complexes were examined. Complexes exhibited V6III crystal structure and compact structure.